Pengaruh Citra Merek dan Harga terhadap Keputusan Pembeian Sepeda Motor Second di Kabupaten Demak - Krisna Bayu; Rodhiyah Rodhiyah (Jurnal Ilmu Administrasi Bisnis, 2016)
Brand image and price is important factor in purchasing decision ofsecondmotorcycle in Demak. Motorcycles as basic needs, but the uneven incomesbecome obstacles for people to buy a new motorcycle, and switched from a newmotorcycle to secondmotorcycle in which a showroom.The purpose of the study, to know the influence of brand image and the priceof purchasing a motorcycle second in Demak. The type of research used explanatoryresearch with sample 100 respondents who already bought a second motorbike in theshowroom at Demak. The Sampling technique used accidental sampling andpurposive sampling.Results and discussion. The majority of respondents (74%) said a good brandimage, but a small proportion of respondents (8%) said was good enough. Mostrespondents (80%) said affordable, however there is a small proportion ofrespondents (13%) stated quite affordable. The majority of respondents (62%) saidthe high purchasing decision, but there is a small proportion (1%) respondentsexpressed low. Theres the influence of brand image against a purchasing decision,evidenced by the results of the calculation of the correlation analysis test of 0.293with the level low, contributing brand image towards purchasing decision onlyamounted to 8,6%. There is the influence of the price of the purchase, evidenced bythe correlation analysis test of 0.262 with level low, the contribution rates againstpurchasing decision only amounted to 6,9%. There is the influence of the brandimage and price of purchase, evidenced by the correlation analysis test 0.332 withlevel low. contributions to the brand image and price of purchase amounted to 11%.Conclusions and suggestions, there is a positive influence between brandimage and price of purchase decisions partially or simultaneous. Recommended forbusiness owners of showroom for maintaining and observing the quality of thesecond motorcycle, because consumers choose a motorcycle second because of itsquality.